Courteous exchanges: Spenser's and Shakespeare's gentle dialogues with readers and audiences - Wareh, Patricia (The Manchester Spenser Series, 2024)
This book offers new connections between Spenser and Shakespeare by showing how their works hone readers' and audiences' judgement about the social construction of aristocratic identity.